ChemInform Abstract: Trichloromethyl Ketones: Asymmetric Transfer Hydrogenation and Subsequent Jocic‐Type Reactions with Amines. Issue 8 (25th February 2014) - Perryman, Michael S.; Harris, Matthew E.; Foster, Jade L.; Joshi, Anushka; Clarkson, Guy J.; Fox, David J.
Abstract Asymmetric transfer hydrogenation of trichloromethyl ketones (I) is achieved using a Noyori‐type ruthenium‐complex as catalyst.